TINGKAT KEPUASAN PELANGGAN AKAN PELAYANAN TRANSJAKARTA DI HALTE CAWANG SAAT RUSH HOUR - Sabrina Ahmad; Audy Adriani, Reno Susetyo Bambang Nugroho, Panca Adjie Pamungkas (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research was conducted at Cawang Bus Stop, Jakarta, to evaluate customer satisfaction levels using loyalty as an indicator. Public transportation plays a vital role in mobility, aiming to reduce congestion and provide efficient transportation alternatives. In Jakarta, Transjakarta, a BRT system, serves as the primary solution for the community's transportation needs. However, the main challenge is maintaining customer satisfaction, especially during rush hours, where Cawang Bus Stop often experiences a surge in passengers. The customer satisfaction theory measures satisfaction based on the comparison between customer expectations and perceived performance (Oliver, 1980). Research methods include field surveys and distributing questionnaires to 10-20 service users at Cawang Bus Stop. The Customer Satisfaction Index (CSI) technique is utilized to measure overall satisfaction levels, considering the relevance of each service element. The research findings indicate that punctuality of departure schedules and bus service quality are the primary factors influencing passenger satisfaction. The obtained CSI is 79.83%, indicating that the level of customer satisfaction falls within the "Satisfied" category. These findings are expected to be utilized by PT Transjakarta to enhance their services during rush hours and contribute both practically and academically to the fields of transportation studies and public service management